Analysis of Geometry Concept Sequence in Student Textbooks Based on Van Hiele's Theory - Janah, Miftakul; Rahardi, Rustanto; Rahardjo, Swasono (PRISMA, 2024)
This study aims to analyze the order of textbooks based on van Hiele's theory. The research approach used is descriptive qualitative. The method used is content analysis or content study. The data subject in this research is junior high school mathematics textbook grade VIII curriculum 2013. The research was conducted by looking at the suitability of the characteristics at each van Hiele level with the textbook. Then if a discrepancy is found in the analysis, a solution is given according tZo the researcher's skills. The results showed that in general all the material "Surface Area of Cuboid and Cubes" in the Mathematics textbook of junior high school grade VIII curriculum 2013 material on the concept of surface area of cuboid and cubes has not fulfilled the order based on van Hiele's theory as a whole, namely there is an incomplete explanation in each level. The level of sequence analyzed in this textbook reaches level 2 (Ordering). So it is recommended for future research that the results of this analysis be used as a reference in teaching geometry material to students.